Dynamic friction transmission and creep characteristics between hoisting rope and friction lining. (November 2015) - Wang, Dagang; Zhang, Dekun; Mao, Xianbiao; Peng, Yuxing; Ge, Shirong
Abstract: Dynamic friction transmission and creep characteristics between the rope and friction lining during deep coal mine hoisting were presented in this study. Rope tensions during lifting and lowering were obtained applying Simulink simulation models. Effects of the effective payload, maximum speed, acceleration and deceleration on dynamic friction transmission and creep properties were explored. The results show that increases of the effective load, maximum speed, acceleration and deceleration almost all induce expanding trends of overall ranges of the active slip angle, maximum creep amplitude and maximum creep velocity, respectively. Highlights: Evolutions of slip states between the rope and friction lining were presented. Roles of kinematic parameters on evolutions of slip states were explored. Roles of effective load on evolutions of slip states were exhibited. Evolutions of creep amplitude and creep velocity during hoisting were discussed. Roles of kinematic and kinetic parameters on dynamic creep properties were studied.